(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we study hesitant fuzzy sets and some of its properties .We introduce the notions of hesitant fuzzy ideal, hesitant fuzzy prime ideal of a ring and hesitant fuzzy strongly prime ideal ,hesitant fuzzy 3- prime ideals . And we give a characterization of hesitant fuzzy prime ideal ,also introduce relationships between hesitant prime ideal and strongly prime ,3-prime . And some important basic operation on the hesitant fuzzy prime ideal of a ring .